INTEGRATED POPULATED SERVICES SYSTEM USING AGILE APPROACH - Agus Qomaruddin Munir; Evrita Lusiana Utari; Desty Ervira Puspaningtyas; Bayu Indra Wahyudi (Jurnal Teknik Informatika (Jutif), 2023)
The significant and uneven population growth in Indonesia in each region triggers problems for implementing development. The government has tried to overcome various population problems, one of which is using electronic media to record and update population biodata in population administration in Indonesia, namely establishing a Population Administration Information System (SIAK). The goal is that all people can be recorded and recorded accurately in the SIAK database and have a Population Identification Number (NIK) which is helpful as a reference for the government in providing public services to the community, one of which is population services at the village level. Kelurahan is a government agency under the sub-district, led by the village head. Kelurahan consists of several RW, and each RW consists of several RT. For this reason, a government agency requires a system that can assist and facilitate agency devices, so a system is needed, namely a population information system in the Village. This study aims to make an Integrated Population Information System at the Kalurahan level. The Population Information System includes data services for new residents, birth data, death data, moving data, arrival date, and marriage data. The information system is accessed using mobile devices that have easy access for residents. The software development method used is a serial waterfall which starts from the system's planning, analysis, design, and implementation process. The output of this research is an applicative work for using research-based information technology to assist population services where the Integrated Population Service System can be accessed using a mobile application. Digitized data can be used as a basis for information retrieval, one of which is the opportunity to make efforts to facilitate population services through the information collected.